Impact of body fitness (bodybuilding) classes on the manifestation of the physical qualities of athletes for 15-17 years - Diana Bielska; Victor Dzhym; Vadim Voronetsky (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to establish the dependence on the influence of 15-17 year old female athletes involved in body fitness (bodybuilding) on the manifestation of physical qualities during the annual macrocycle at the stage of preliminary basic training. Material and methods: the research was carried out in fitness clubs: «Tetra», «Record», «Misto», «Ford» of Kharkov, with athletes 15-17 years old, engaged in body fitness (bodybuilding) during an annual macrocycle in the amount of 20 people. All athletes trained according to the classic program designed for body fitness (bodybuilding). The following methods of research were used: analysis of literary sources and testing of the level of motor qualities in certain age categories. Results: presented pedagogical testing to determine the level of motor abilities of young athletes 15-17 years old, engaged in body fitness (bodybuilding). Exercises were identified that are advisable to use at these stages of preparation: burpe (number of times in 30 s); jumping rope (number of times in 30 s); raising the body from a supine position (number of times in 40 s); jumping lunges (number of times in 30 s); running 30 m (s); flexion and extension of the arms (wringing) in the TRX simulator (number of times in 40 s); bending forward from a sitting position (sm). Conclusions: as a result of testing motor qualities using nonspecific exercises for body fitness (bodybuilding), it was found that indicators improve every year in all exercises (p> 0,05), especially in the exercise of raising the trunk. lying on his back, the number of times in 40 s, which significantly increased in the age range from 15 to 17 years. The speed-strength abilities of young athletes of 15-17 years old, engaged in body fitness (bodybuilding), were manifested to a greater extent in the age interval from 16 to 17 years.